Acute effects from the half-squat performed using a repetition versus differential approach in youth soccer players - Diogo Coutinho; Eduardo Abade; Bruno Gonçalves; Sara Santos; Wolfgang Schöllhorn; Jaime Sampaio (BMC, 2022)
Abstract Background Over the last years there have been a wide body of research exploring the best strategies to promote acute enhancements in players' performance. Despite that, most studies have been focused on adult and elite players, and different results may be identified when considering players from lower levels of performance and belonging to youth categories. In addition, most studies conducted in this domain focused in repetitive movement patterns, and while adding variability has been considered as a useful approach to enhance players' performance at short and long-term perspectives, less is known regarding it applicability to acute enhance players physical performance. Therefore, this study aimed to compare the acute enhancement effects of performing the half-squat in a flywheel ergometer between a more-repetitive approach (low noise) and a more variable approach (differential learning, high noise) in youth soccer players. Methods A total of sixteen players (age = 16.2 ± 0.6 years) was exposed to four conditions in a randomized order: (1) repetitive intervention for 30 s; (2) repetitive intervention for 10-min; (3) differential learning intervention for 30 s; (4) differential learning intervention for 10-min. Each condition consisted in 3 sets of 6 repetitions of eccentric half squats performed in a flywheel ergometer. Countermovement jump, 10 m and 30 m linear sprint, and change-of-direction ability were measured every session at baseline (pre-test) and after each protocol (post-test). Results No potentiation effect was observed overall with any of the interventions. In addition, no differences between protocols were found for sprinting. However, the repetitive intervention impaired jumping performance for both 30 s (small effects, p ≤ .05) and 10-min intervals (small effects, p ≤ .05), as well as in the change-of-direction task for 30 s (p ≤ .05). Conclusions These results may be due to the players' low experience in eccentric flywheel training. Despite these findings, individual potentiation responses emerged from both protocols when considering the individual responses, reinforcing the need to establish more personalized approaches.